Proline utilization in Saccharomyces cerevisiae: analysis of the cloned PUT2 gene. - Brandriss, M C (1983)
The PUT2 gene was isolated on a 6.5-kilobase insert of a recombinant DNA plasmid by functional complementation of a put2 (delta 1-pyrroline-5-carboxylate dehydrogenase-deficient) mutation in Saccharomyces cerevisiae. Its identity was confirmed by a gene disruption technique in which the chromosomal PUT2+ gene was replaced by plasmid DNA carrying the put2 gene into which the S. cerevisiae HIS3+ gene had been inserted. The cloned PUT2 gene was used to probe specific mRNA levels: full induction of the PUT2 gene resulted in a 15-fold increase over the uninduced level. The PUT2-specific mRNA was approximately 2 kilobases in length and was used in S1 nuclease protection experiments to locate the gene to a 3-kilobase HindIII fragment. When delta 1-pyrroline-5-carboxylate dehydrogenase activity levels were measured in strains carrying the original plasmid, as well as in subclones, similar induction ratios were found as compared with enzyme levels in haploid yeast strains. Effects due to increased copy number or position were also seen. The cloned gene on a 2 mu-containing vector was used to map the PUT2 gene to chromosome VIII.